The artistic phenomenon between the aesthetic dimension and the proof of being and identity - Rahab, Mokhtar (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The scientific interest has focused on studying societies, peoples and cultures for a long time, and among the scientific interests in this field is the diagnosis and study of the relationship between arts and social reality, especially in the scope of daily interaction of individuals and what functions the arts with their various forms and types perform positively on the lives of individuals, through imparting aesthetic dimensions, material benefits, as well as strong symbolic functions associated with individual and group identity. It also supports the meaning of life in its aesthetic dimension, its existential significance, and the reinforcement of the meanings of happiness in human life. Arts of many people at different periods of time formed an effective tool within the project of defense and resistance, contributing to societal self-assertion and consolidating the elements of the national character against imperialism, domination, subjugation and control attempts. This is in addition to the use of arts of all kinds as a tool for civilized communication between cultures and societies and the consolidation of principles of coexistence and dialogue among people, especially in our present time. In our article, we will try to highlight the aesthetic and material dimensions and functions of the arts in the life of societies.